ANALISIS MANAJEMEN DAN ESTIMASI BIAYA PEMELIHARAAN GEDUNG KANTOR BUPATI DAN DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN PAMEKASAN - Destia Nurulita Sari; Jojok Widodo Soetjipto; Syamsul Arifin (Fakultas Teknik, Universitas Wiraraja, 2022)
According to the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 article 1 paragraph 2, building maintenance is an activity to maintain the reliability of the building along with its infrastructure and facilities so that the building is always functional. The Building Regent's Office and DPRD of Pamekasan Regency are more than ten years old, and visually some damage has begun to appear in the building. This study aims to determine the maintenance management and budget plan for Regents' Office and Legislative Regional Office Building in Pamekasan Regency. This research refers to the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 concerning Guidelines for Building Maintenance and Maintenance. This research use data which get measured directly in the field, collecting data from the Head of the Maintenance Unit and filling out the damage form for the Minister of Public Works 16/PRT/M/2016 by looking directly at the field and interviews. The analysis show that Standard Operating Procedure in building maintenance does not fulfill the regulation; the deterioration is minor and doesn't influence the functional building. This deterioration category is suitable with budget to maintain the building based on Public Work minister regulation.